Pengurusan perpustakaan Muslim abad ke 8-19 Masihi: satu pengenalan - Tamjehi, Haslan; Ramli, Latifah (Persatuan Pustakawan Malaysia, 2015)
Muslim libraries have undergone a long comprehensive history. Its existence which began since 6th century A.D. are recorded in written sources by Muslims and orientalists. Some of the sources are preserved until today as precious knowledge and intellectual heritage of human civilization. Hence, this writing introduces the unique aspects of Muslim libraries during Islamic period until 19th century A.D. in collection development, cataloging and circulation. The details of those aspects are illustrated to understand its management and practice within the specified period.